Safety requirements for cableway installations designed to carry persons - Carries Part 2. Slipping resistance test for grips (BSI, 2005)
Cableways, Aerial ropeways, Passenger ropeways, Equipment safety, Passenger transport, Monocable ropeways, Bicable ropeways, Safety measures, Grasping devices, Slip, Test methods, Materials handling components, Aerial equipment, Drag lifts